Impacts of 2018 drought on agriculture in the UK - Interview responses - Hess, Tim M.; Holman, Ian P.; Knox, Jerry W. (Cranfield University, 2021)
Summarised responses from interviewees on the impacts of drought in 2018 on agriculture and potential strategies for mitigation. The responses have been anonymised and and information that could be used to identify individuals of businesses has been redacted.
Keywords: drought resistance'; 'irrigated farmland'; 'Agricultural Hydrology (Drainage; Flooding; Irrigation; Quality; etc.)'